HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN HYGIENE SANITASI PANGAN (HSP) PADA SISWA KELAS IV DAN V SDN TUNYANG KECAMATAN TIMANG GAJAH KABUPATEN BENER MERIAH - Tona Iwan Sara; Khairuddin; Nurlaely HS (Jurnal Ilmiah Cerebral Medika, 2026)
ABSTRACTFood safety is not only a world issue but also concerns individual concerns. There are several factors that affect the occurrence of food poisoning, including poor personal hygiene, unhealthy food handling methods and unclean food processing equipment. One of the reasons is due to a lack of knowledge in paying attention to one's own health and the environment in a good and healthy food processing process. This study aims to determine the Relationship between Knowledge and Attitudes with Food Hygiene Hygiene Measures (HSP) in Grade IV and V Students of SD Negeri Tunyang, Timang Gajah District, Bener Meriah Regency in 2024. This type of research is analytical with a cross sectional design. The population in this study is all students in grades IV and V at SD Negeri Tunyang, Timang Gajah District, Bener Meriah Regency as many as 51 students. Sampling was carried out by means of total sampling, where the entire population was sampled. The research was conducted from August 10 to 21, 2024 using a questionnaire. From the results of this study, it was shown that the results of the Chi Square statistical test and at the 95% confidence level were carried out to determine the relationship between knowledge and food hygiene and sanitation, a P Value of 0.000 (P ≤ 0.05) was obtained and the relationship between attitudes and food hygiene and sanitation, a P Value of 0.000 (P ≤ 0.05) was obtained. This statistically shows that there is a meaningful relationship between attitudes and food sanitation hygiene. It is recommended for students to be able to apply sanitary hygiene to their food so as to avoid diseases due to lack of hygiene in food. Keywords : Knowledge, Attitude, Hygiene Food Sanitation